Organizational Commitment of the Millennial Generation Workforce in Indonesian Higher Education: Systematic Literature Review - Muhammad Ridlo Zarkasyi (STAI Hubbulwathan Duri, 2024)
This paper aims to offer a thorough review of research on the factors influencing organizational commitment among the millennial workforce in Indonesian higher education. The review specifically addresses the key questions of identifying the main factors affecting organizational commitment in the millennial workforce in Indonesian higher education and examining how knowledge sharing relates to organizational commitment among these millennial employees. The criteria for selecting the 50 research articles included a requirement that they be peer-reviewed and published in either English or Indonesian. Exclusion criteria were applied to filter out non-peer-reviewed sources and articles not focused on the specified demographic. The articles were sourced from electronic scientific databases, including Google Scholar, Scopus, and Web of Science, using search terms such as